Comparison of the hybrid capture tube test and PCR for detection of human papillomavirus DNA in cervical specimens. - Cope, J U (1997)
The strong association of human papillomavirus (HPV) and cervical cancer makes it important to study HPV detection methods that may play a role in cervical cancer screening. We compared two DNA methods that are commonly used for HPV research in the United States: the MY09/MY11 L1 consensus primer PCR-based test and the first-generation Hybrid Capture tube method (HCT). Laboratory assays by each method were performed with 596 cervicovaginal specimens collected from participants in a large cohort study conducted in Portland, Oreg. Included were 499 specimens from women whose cytology was normal and 97 specimens from women with squamous intraepithelial lesions (SILs). The overall HPV DNA positivity for known types was 22.5% by PCR compared to 13.6% by HCT. When the analysis was restricted to the 14 HPV types detectable by both methods, the sensitivity of HCT, with PCR used as the standard for HPV status, was higher for specimens from women with concurrent SILs (81.0%) than for specimens from women with normal cytology (46.7%). Among specimens testing positive by both methods, 97.2% of the time the two methods agreed on whether specimens were positive for cancer-associated HPV types. Both of these HPV test methods provide information that supplements the information provided by the Pap smear. The PCR method has higher analytic sensitivity than HCT in detecting HPV, but HCT may be helpful in identifying women with concurrent SILs.